2022
DOI: 10.1002/csc2.20852
|View full text |Cite
|
Sign up to set email alerts
|

Soybean growth and production as affected by struvite as a phosphorus source in eastern Arkansas

Abstract: Struvite (MgNH 4 PO 4 •6H 2 O) has been precipitated from liquid waste streams to recover valuable nutrients, such as phosphorus (P) and nitrogen (N), that can be used as an alternative fertilizer-P source. Because prior research has focused on greenhouse studies, it is necessary to expand struvite evaluations to the field-scale to include row-crop responses. The objective of this field study was to evaluate the effects of two struvite materials (electrochemically precipitated struvite, ECST; and chemically pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 42 publications
2
16
4
Order By: Relevance
“…Furthermore, effluents containing high concentrations of P and nitrogen (N) have led to eutrophication in receiving waters . Struvite is recognized as a sustainable slow-release fertilizer, and companies have successfully produced struvite fertilizer via chemical precipitation. These dedicated units require expensive magnesium (Mg) salts and pH additives.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, effluents containing high concentrations of P and nitrogen (N) have led to eutrophication in receiving waters . Struvite is recognized as a sustainable slow-release fertilizer, and companies have successfully produced struvite fertilizer via chemical precipitation. These dedicated units require expensive magnesium (Mg) salts and pH additives.…”
Section: Introductionmentioning
confidence: 99%
“…(2022), and Omidire et al. (2023) encountered and overcame the same limited‐quantity issue in several recent field studies, which substantiated an initial study in the greenhouse before moving to the field. Furthermore, greenhouse studies allow for treatment evaluations in a more‐controlled environment than in the field, limiting potential confounding variables, and can guide the development and design of field studies based on some degree of prior knowledge (van Es et al., 2007).…”
Section: Introductionmentioning
confidence: 81%
“…Second, the ECST material evaluated in this study is still experimental, such that only a limited quantity was available for testing; thus, a greenhouse study facilitated the judicious use of the ECST, while still being able to conduct a meaningful comparative study. , Omidire, Brye, English, et al (2022), andOmidire et al (2023) encountered and overcame the same limited-quantity issue in several recent field studies, which substantiated an initial study in the greenhouse before moving to the field. Furthermore, greenhouse studies allow for treatment evaluations in a morecontrolled environment than in the field, limiting potential confounding variables, and can guide the development and design of field studies based on some degree of prior knowledge (van Es et al, 2007).…”
Section: Core Ideasmentioning
confidence: 89%
“…Although struvite has been reported to have slow-release properties because of struvite's low solubility in water and greater solubility with increasing acidity [19], results of this study indicated that ECST exhibits fertilizer-P behavior that is comparable to commercially available CPST and other commonly used fertilizer-P sources, such as MAP and TSP, in a range of soil textures. Consequently, struvite can be used directly as fertilizer-P source for agricultural production among numerous crops [28] [29] [30].…”
Section: Discussionmentioning
confidence: 99%
“…The ECST shares similar characteristics as the chemically precipitated struvite (CPST), like its partial solubility in water, but increasing solubility with a decrease in pH, and also the ability to increase soil pH over time [3] [19]. However, struvite precipitation and crystal formation are impacted by several factors, such as Mg 2+ , crop production [2] [3] [7] [13] [19] [21]- [30], commercially available CPST's dissolution dynamics have been studied in a series of plant-less, moist-soil incubation experiments in Arkansas loam, silt loam, and silty clay loam soils. The fertilizer-P materials used and compared included finely ground and pelletized CPST, MAP, DAP, TSP, and rock phosphate to determine their fertilizer-P behavior over a 6-month period in several Arkansas soils [31] [32] [33].…”
Section: Introductionmentioning
confidence: 99%